Lizards in pinstripes: morphological and genomic evidence for two new species of scincid lizards within Ctenotus piankai Storr and C. duricola Storr (Reptilia: Scincidae) in the Australian arid zone - Rabosky, Daniel L.; Doughty, Paul; Huang, Huateng (Zootaxa, 2017)
The scincid lizard genus Ctenotus is one of the most species-rich genera of squamate reptiles, but few molecular phylogenetic studies have been undertaken on the group. Here we assess molecular and morphological variation within C. piankai and C. duricola, an arid-adapted pair of nominate species characterized by a pattern of thin pale longitudinal lines on a dark background that occur primarily in the western deserts and Pilbara region of Australia. We sequenced mitochondrial DNA and genome-wide restriction-site associated DNA (RAD) from geographically widespread samples of these lizard taxa, with particularly dense sampling from the Pilbara region. Phylogenetic analyses of the mitochondrial cytochrome B gene and approximately 5,000 nuclear loci identified four highly divergent lineages within the two taxa. The four genetically-defined populations were concordant with geography and are distinguishable based on multiple morphological and color pattern characters, despite appearing superficially similar in appearance. Despite limited mtDNA exchange between two lineages in the Pilbara, we found no evidence for ongoing gene flow across the nuclear genome. For the western desert lineages, there was no evidence of introgression for either mtDNA or nDNA in our data. To resolve the taxonomy of the group, we redescribe C. piankai and C. duricola, and recognize the two divergent lineages as new species: C. rhabdotus sp. nov., from the south-eastern Kimberley, Ord, Victoria River and northern Tanami Desert regions of Western Australia and the Northern Territory, and C. pallasotus sp. nov., from the western Pilbara and North West Cape regions of Western Australia.